SO-M2 Game (Social Multiplication Math Game) sebagai media menghafal perkalian pada siswa-siswi sekolah dasar - Nur’aini, Luthfiah Hamidah (Maliki Interdisciplinary Journal, 2024)
Mathematics is a universal science that has an important role in various disciplines and encourages the advancement of human thinking. Likewise, in learning, mathematics is also one of the subjects that demands critical, analytical, logical, and systematic thinking. However, some facts in schools state that understanding of mathematical concepts in students is still lacking. Mathematics is still considered a difficult and meaningless subject. Interest in learning becomes an important thing in learning. But the results of international surveys such as PISA show that interest in mathematics in Indonesia is still relatively low. One of the causes is the lack of innovations in learning. Therefore, the "SO-M2 GAME" program is a solution to overcome this problem. This program is a game using card media pictures of Islamic mathematicians. "SO-M2 GAME" can indirectly improve fast counting skills and can be done easily and fun.